Analisis Financial Distress Pada 4 Perusahaan Perkebunan Kelapa Sawit Tahun 2022-2023 Berdasarkan Trend Harga Saham Dan Analisis Metode Altman Z-Score - Aris Triartadi; Nurul Huda (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2025)
This research aims to analyze the level of financial distress in four palm oil plantation companies listed on the Indonesia Stock Exchange (BEI) during the 2022-2023 period, using the Altman Z-Score method. The basis for selecting companies as sampling is the criteria for companies whose share price trends are below IDR 500 per share. In addition, this research evaluates the relationship between stock price trends and company financial conditions as a reflection of market sentiment on business performance. The results of the analysis show that two companies are in the financial distress zone, one company is in extreme conditions with a high risk of bankruptcy, and one company is in the safe zone with stable financial performance. It was found that companies with low Z-Score values ​​tend to have stagnant or declining share prices, while companies in the safe zone show more stable share prices. This research provides insight for management, investors and policy makers to understand the relationship between financial risks and market trends, as well as design mitigation strategies to maintain business sustainability in the palm oil plantation sector